Transcatheter aortic valve implantation in elderly patients with severe aortic stenosis and rheumatic phenotype - Elkaialy, Ahmed Abdelrahman; Farag, Nabil; Mostafa, Ahmad Elsayed; Baraka, Mahmoud; Kamal, Diaa (Cardiovascular intervention and therapeutics, 2025)
Significant fibrosis is characteristic of rheumatic aortic valve disease that affects anchoring and deployment of the trans-catheter heart valve. Our goal was to determine whether trans-catheter aortic valve implantation (TAVI) is an effective treatment option for severe aortic stenosis patients with rheumatic valvular disease. This study is a prospective cohort study that includes a total of 54 rheumatic severe aortic stenosis patients who were referred for TAVI. The age ranged from 65.00 to 83.00 years (mean age 72.75 ± 5.86 years). Notably, 63% of the patients had undergone preimplantation balloon dilatation. The outcomes included total new conduction disturbances (transient and permanent defects of atrio-ventricular block and left bundle branch block) in 31.4% of the patients, permanent pacemaker implantation in 3.7%, and valve embolization in 1.85%, and no patients had moderate to severe para-valvular leak. All-cause death within a 6-month follow-up was 3.7%. This cohort was then compared to a propensity score matched group of degenerative calcific severe aortic stenosis of 54 cases revealing comparable post-procedural results. Compared with the outcomes of TAVI in patients with degenerative aortic stenosis, TAVI represents a viable and durable option for rheumatic severe aortic stenosis patients. Graphical abstract